2023
DOI: 10.30595/jhes.v6i1.16738
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Layanan dan Citra Merek Terhadap Loyalitas Nasabah BCA Syariah dengan Kepuasan Nasabah sebagai Variabel

Abstract: Penelitian ini bertujuan untuk mengetahui apakah kualitas pelayanan dan citra merek berpengaruh terhadap loyalitas nasabah, dengan kepuasan nasabah sebagai variabel mediasi. Sampel untuk penelitian ini adalah 114 nasabah yang diambil dari basis nasabah. Metode pengumpulan data menggunakan kuesioner yang disebarkan menggunakan Google Forms dan wawancara tatap muka. Metode penelitian yang digunakan adalah teknik purposive sampling. Data yang diperoleh dari kuesioner kemudian diolah dan dianalisis dengan mengguna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Consistent with the research conducted by Sayekti and Dwiridotjahjono (2022), it has been demonstrated that brand image substantially influences consumer loyalty using consumer satisfaction. (Prasetyo et al, 2023) asserted that brand image indirectly impacts customer loyalty by affecting consumer satisfaction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with the research conducted by Sayekti and Dwiridotjahjono (2022), it has been demonstrated that brand image substantially influences consumer loyalty using consumer satisfaction. (Prasetyo et al, 2023) asserted that brand image indirectly impacts customer loyalty by affecting consumer satisfaction.…”
Section: Resultsmentioning
confidence: 99%
“…Research indicates that brand image exerts a substantial impact on consumer loyalty using consumer happiness. (Prasetyo et al, 2023;Rahmadani & Dwiridotjahjono, 2023) Have presented research findings that differ from those of other studies. Specifically, they suggest that brand image does not substantially impact customer loyalty when mediated by customer satisfaction (Indraswari & Susanti, 2023).…”
Section: Introductionmentioning
confidence: 83%
“…It has been demonstrated that there are five aspects of service quality that can boost customer loyalty: tangibles, assurance, responsiveness, consistency, and empathy (Salimah, 2018). In theory, the process's service quality can be used as a benchmark for this study since it directly affects customer loyalty without the need for other mediators (Prasetyo et al, 2023). A company's ability to survive depends on its ability to provide high-quality services that satisfy customers (Normasari dkk, 2013).…”
Section: The Influence Of Service Quality On Customer Loyaltymentioning
confidence: 99%
“…However, to get loyalty, sharia banking does not necessarily get it straight away but provides the best service to achieve company goals. Research from (Widnyana & Suarmanayasa, 2021;Prasetyo et al, 2023) demonstrates the favorable and substantial impact that service quality has on client loyalty. However, a study by Satria & Dyah Astarini (2023) demonstrates that customer loyalty is not significantly impacted by service quality.…”
Section: Introductionmentioning
confidence: 99%
“…Penerapan Budaya syariah untuk membangun dan menciptakan budaya perusahaan yang Islami dan adanya peran budaya syariah untuk perusahaan untuk membentuk kepribadian setiap karyawan yang bekerja di lembaga keuangan syariah. Agar budaya perusahaan menjadi landasan karyawan untuk menerapkan SOP yang telah ditetapkan (Siswanto et al, 2020) Bersikap ramah terhadap pelanggan, Hasil penelitian Nadia Ananda syahranie apabila perusahaan mempunyai kualitas layanan yang baik kepada nasabah akan memberikan peningkatan kepuasan nasabah dan menimbulkan persepesi yang baik dar nasabah terhadap perusahaan (Syahranie et al, 2020). Berbusana yang syar'i (sesuai syariah), tempat kerja yang nyaman, membaca doa sebelum bekerja dan sesudah kerja, pemahaman dan pengalaman akidah yang lurus, pemahaman dan pengamalan ibadah yang shahihah, pemahaman dan pengamalan akhlakul karimah, pemahaman Al-qur'an ,Pemahaman fikrah Islamiyah.…”
Section: Analisis Penerapan Manajemen Sdi DI Koperasi Syariah Mt Al A...unclassified